Protestant women in the late Soviet era: gender, authority, and dissent. Issue 2 (2nd April 2016) - Beliakova, Nadezhda; Dobson, Miriam
ABSTRACT: At the peak of the anti-religious campaigns under Nikita Khrushchev, communist propaganda depicted women believers as either naïve dupes, tricked by the clergy, or as depraved fanatics; the Protestant "sektantka" (female sectarian) was a particularly prominent folk-devil. In fact, as this article shows, women's position within Protestant communities was far more complex than either of these mythical figures would have one believe. The authors explore four important, but contested, female roles: women as leaders of worship, particularly in remote congregations where female believers vastly outnumbered their male counterparts; women as unofficial prophetesses, primarily within Pentecostal groups; women as mothers, replenishing congregations through high birth rates and commitment to their children's religious upbringing; and women as political actors in the defence of religious rights. Using a wide range of sources, which include reports written by state officials, articles in the church journal, letters from church members to their ecclesiastical leaders in Moscow, samizdat texts, and oral history accounts, the authors probe women's relationship with authority, in terms of both the authority of the (male) ministry within the church, and the authority of the Soviet state.